2020
DOI: 10.1590/s1677-5538.ibju.2019.0230
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of automated irrigation systems using an in vitro ureteroscopy model

Abstract: Introduction: Two automated irrigation systems have been released for use during endoscopic procedures such as ureteroscopy: the Cogentix RocaFlow® (CRF) and Thermedx FluidSmart® (TFS). Accurate pressure control using automated systems may help providers maintain irrigation pressures within a safe range while also providing clear visualization. Our objective was to directly compare these systems based on their pressure accuracy, pressure-fl ow relationships, and fl uid heating capabilities in order to help pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…11 While there are no data on the most commonly chosen irrigation pressures in North America, a recent bench study of automated irrigation systems conducted by urologists in the United States were done at pressure settings with a maximum of 300 mmHg to mimic clinical practice. 12 In another US bench study where a setting of 200 mmHg with the pressurized saline bag was used, it was noted that a pressure in excess of 300 mmHg may occur in the operating room. 13 We found that North American practice was different to that in Europe where most surgeons used pressurized saline and practiced more uniformly; it was the only region to have more than half of all respondents prefer one irrigation method.…”
Section: Discussionmentioning
confidence: 99%
“…11 While there are no data on the most commonly chosen irrigation pressures in North America, a recent bench study of automated irrigation systems conducted by urologists in the United States were done at pressure settings with a maximum of 300 mmHg to mimic clinical practice. 12 In another US bench study where a setting of 200 mmHg with the pressurized saline bag was used, it was noted that a pressure in excess of 300 mmHg may occur in the operating room. 13 We found that North American practice was different to that in Europe where most surgeons used pressurized saline and practiced more uniformly; it was the only region to have more than half of all respondents prefer one irrigation method.…”
Section: Discussionmentioning
confidence: 99%
“… 26–28 Alternatively, automated irrigation systems have been shown to provide steady irrigation at safe pressures with better visibility 29–31 There are different types of automatic irrigation pumps include Uromat Pump, Thermedx FluidSmart (TFS) ® and the Cogentix RocaFlow (CRF) ® . 30 …”
Section: Irrigation Systemmentioning
confidence: 99%